2021
DOI: 10.21608/mnj.2021.213159
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture, Individual Innovation and their relation to Nursing Staff’s Work Engagement

Abstract: Background: Organizational culture supports nursing staff in their organization and significantly improves their individual innovation and work engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…In the same line [ 36 ] who indicated that every nurse must become aware of the resources available in their practice environment for handling any ethical dilemmas, learn how to use them, and work with their coworkers. Similarly, these findings were consistent with [ 37 ] who cleared that all domains of the organizational culture (which build group cohesiveness) was significantly correlated with individual innovation.…”
Section: Discussionsupporting
confidence: 91%
“…In the same line [ 36 ] who indicated that every nurse must become aware of the resources available in their practice environment for handling any ethical dilemmas, learn how to use them, and work with their coworkers. Similarly, these findings were consistent with [ 37 ] who cleared that all domains of the organizational culture (which build group cohesiveness) was significantly correlated with individual innovation.…”
Section: Discussionsupporting
confidence: 91%
“…The importance and necessity of managerial support in supporting employees' individual innovativeness are supported by various studies (Afsar & Umrani, 2020;Palumbo, 2021;Zappalà et al, 2020). According to a study conducted on nurses, it is recommended to develop a mentoring program in which experienced nurses act as models and mentors to empower and motivate new nurses in the profession (el Desoky et al, 2021). Although this study was carried out on nurses, it can also be considered for specialist doctors and intern doctors or specialist health personnel and new health personnel.…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized in many studies that individual creativity positively affects innovation (Liu & Zeinaly, 2020;Oppi et al, 2019). It is recommended to provide creative and innovative problem-solving training to employees to support individual creative thinking (el Desoky et al, 2021). At the same time, it is recommended to inspire useful ideas to encourage innovative thinking and to develop mechanisms and procedures that facilitate changes in traditional task performances (Oppi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, El Desoky et. al., (28) stated that head nurses had high level of innovative work behaviors at Kafr El Sheikh University Hospital.…”
Section: Discussionmentioning
confidence: 99%